Towards a Literary Transmediality as a Didactic Resource for Reading Motivation - Castro Rojas, Jósebeth (2022)
The enjoyment of literature goes hand in hand with the motivation it has.  It is a challenge to get adolescents interested in reading and to be able to understand literature as an ally for entertainment and not as an obligation. To get students excited, it is important to generate new ways of approaching the text, and transmedia studies are a good tool to achieve this. Through adaptations of literary texts into comics, the student learns a new way of appreciating literature and enjoying the stories, which is why the proposal to work on a story by Edgar Allan Poe and its respective adaptation into comics was generated as a central axis for reading motivation.